Nutritional Impact and Its Potential Consequences on COVID-19 Severity - Mortaz, Esmaeil; Bezemer, Gillina; Alipoor, Shamila D.; Varahram, Mohammad; Mumby, Sharon; Folkerts, Gert; Garssen, Johan; Adcock, Ian M. (Frontiers in Nutrition, 2021)
Background: During late 2019 a viral disease due to a novel coronavirus was reported in Wuhan, China, which rapidly developed into an exploding pandemic and poses a severe threat to human health all over the world. Until now (Dec 2020), there is no effective treatment or any suitable medication for the management of this global disease. As such, the only way to control the pandemic seems to be having a healthy, strong, and resilient immune system. Nutrition and metabolic disorders such as obesity and diabetes play a crucial role on the community health situation in general and especially during this new pandemic. There seems to be an enormous impact of lifestyle, metabolic disorders, and immune status on COVID-19 disease severity and recovery. For this reason, it is important to consider the impact of lifestyle and the consumption of well-defined healthy diets during the pandemic. Aims: In this review, we summarise recent findings on the effect of nutrition on COVID-19 susceptibility and disease severity and treatment. Understanding how specific dietary features might help to improve the public health strategies to reduce the rate and severity of COVID-19.